Biomimetic myocardial patches fabricated with poly(ɛ‐caprolactone) and polyethylene glycol‐based polyurethanes. Issue 5 (5th December 2013) - Silvestri, Antonella; Sartori, Susanna; Boffito, Monica; Mattu, Clara; Di Rienzo, Anna M.; Boccafoschi, Francesca; Ciardelli, Gianluca
Abstract The production of efficient heart patches for myocardium repair requires the use of biomaterials with high elastomeric properties and controllable biodegradability. To fulfil these design criteria we propose biodegradable poly(ester urethanes) and poly(ether ester urethanes) from poly(ɛ‐caprolactone) (PCL) and poly(ethylene glycol) (PEG) as macrodiols, 1, 4‐diisocyanatobutane as diisocyanate, l‐Lysine Ethyl Ester and Alanine‐Alanine‐Lysine (AAK) as chain extenders. This peptide was used to tune biodegradability properties, since the Alanine–Alanine sequence is a target for the elastase enzyme. Enzymatic degradation tests demonstrated the feasibility of tuning biodegradability properties due to the introduction of AAK peptide in polyurethane backbone. Two formulations have been processed into porous scaffolds by Thermally‐Induced Phase Separation (TIPS). Scanning Electron Microscopy micrographs revealed promising microstructures, which were characterized by stretched and unidirectional pores and mimicked the striated muscle tissue. Tensile tests showed that, although scaffolds are characterized by lower mechanical properties than films, these substrates have suitable elastomeric behaviors and elastic moduli for contractile and soft tissue regeneration. Viability tests on cardiomyocytes revealed the best cell response for dense film and porous scaffold obtained from PCL and Lysine Ethyl Ester‐based polyurethane, with an increased viability for the porous substrate, which is ascribable to the morphological features of its microstructure. Future works will be addressed to study the in vivo behavior of these constructs and to confirm their applicability for myocardial tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.